174k views
1 vote
Consider (11x + 9) − (?) = 6x + 8. Which expression is missing?

A) 5x + 1
B) 5x - 1
C) 4x - 1
D) −5x + 1

User Lucasmo
by
4.7k points

2 Answers

3 votes

Answer:

A

Explanation:

Let's call the missing expression Y.

11x + 9 - Y = 6x + 8

5x + 1 - Y = 0

5x + 1 = Y

Y = 5x + 1

User Bobulous
by
5.3k points
5 votes

Answer:

A)5x + 1

Explanation:

the statement given us:

(11x + 9) − (?) = 6x + 8.

using option A:

(11x + 9) − (5x+1) = 6x + 8

we have:

11x +9 -5x -1

so we have:

6x +8

finally:

6x +8 = 6x +8

User Stuartc
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.